Commercial and industrial Internet of Things applications with the Raspberry Pi : prototyping IoT solutions - Culic, Ioana (Apress L.P., 2020)
Use the Raspberry Pi and modern computing techniques to build industrial Internet of Things systems. Principles and theoretical aspects of IoT technologies combine with hands-on projects leading to detailed descriptions of several industrial IoT applications. This book presents real-life IoT applications based on the Raspberry Pi, beyond the relatively simplistic demos built for educational purposes or hobbyists. You'll make the transition from tinkering with a couple of sensors and simple devices to building fully developed products for commercial use and industrial systems. You'll also work with sensors and actuators, web technologies used for communications in IoT networks, and the large-scale deployment of IoT software solutions. And see how to design these systems as well as maintain them long term. See the Raspberry Pi in a new light that highlights the true industrial potential of the device. Move beyond connecting an LED to the Raspberry Pi and making it blink to actually managing a network of IoT devices.